2019–2020 Florida Citrus Production Guide: Plant Growth Regulators - Tripti Vashisth; W. Chris Oswalt; Mongi Zekri; Fernando M. Alferez; Jamie D. Burrow (EDIS, 2019)
Plant growth regulators (PGRs) are a tool used to manipulate vegetative and reproductive growth, flowering, and fruit growth and development. PGRs have been successfully used in agriculture for decades to amend plant growth characteristics and maximize yield and thus grower profit. This 4-page fact sheet is part of the 2019–2020 Florida Citrus Production Guide. Written by Tripti Vashisth, W. Chris Oswalt, Mongi Zekri, Fernando M. Alferez, and Jamie D. Burrow, and published by the Horticultural Sciences Department, April 2019.